Tumor targeted cancer membrane-camouflaged ultra-small Fe nanoparticles for enhanced collaborative apoptosis and ferroptosis in glioma - Jingchen Wang; Jian Yang; Kang Liu; Jiayu Yuan; Yijie Shi; Hongdan Li; Liang Zhao (Materials Today Bio, 2023)
Glioma is recognized as the most common and aggressive primary brain tumor in adults. Owing to the occurrence of drug resistance and the failure of drug to penetrate the blood-brain barrier (BBB), there is no effective strategy for the treatment of glioma. The main objective of this study was to develop a biomimetic glioma C6 cell membrane (C6M) derived nanovesicles (DOX-FN/C6M-NVs) loaded with doxorubicin (DOX) and ultra-small Fe nanoparticles (FN) for accomplishing the effective brain tumor-targeted delivery of DOX and improving anti-cancer efficacy via inducing collaborative apoptosis and ferroptosis. The findings revealed that employing C6M-NVs as a carrier significantly improved the therapeutic efficacy by enabling evasion of immune surveillance, facilitating targeted drug delivery to tumor sites, and minimizing cardiotoxicity and adverse effects associated with DOX. DOX-FN/C6M-NVs exhibited more potent anti-tumor effects as compared with free DOX by promoting DOX-mediated apoptosis and accelerating ferroptosis via the mediation of FN. This study suggested that DOX-FN/C6M-NVs as the potential inducer of ferroptosis and apoptosis conferred effective tumor suppression in the treatment of glioma.